Thermal conductivity estimation model considering the effect of water saturation explaining the heterogeneity of rock thermal conductivity. (March 2017) - Albert, Katharina; Schulze, Marcellus; Franz, Claudia; Koenigsdorff, Roland; Zosseder, Kai
Highlights: Effective thermal conductivity of dry and water-saturated sandstones, mudstones, and marlstones. Heterogeneity of the thermal conductivity due variation of matrix and pore properties. Effect of water saturation correlates with porosity exponentially. Mixing law model derived from numerical simulation of heat transfer in porous media. Model considering the variation of the effect of water saturation. Abstract: The study presents the statistical data of the effective thermal conductivity (λe ) of sandstones, mudstones, and marlstones from Bavaria, Germany. The measurements were conducted by the Thermal Conductivity Scanner (TCS) for dry and water-saturated conditions at an ambient temperature and pressure. High variation in the λe of sandstones is a result of the variation in matrix and pore properties. In general, the λe increases because of water saturation. However, dissolving clay mineral found during the saturation process might explain the decrease of λe in mudstones and marlstones in some cases. The coefficient δλ is used to describe the influence of water saturation on the λe, which increases with the increasing porosity (ϕ) exponentially. The variance of the δλ-ϕ-correlation and an analysis of small-scale heterogeneity revealed that water saturation also affects the thermal behavior of the matrix. Based on the measured data, the matrix thermal conductivity (λm ) is calculated according to the proposed mixing model, which takes δλ into consideration in order to rectify the impact of water saturation on the λe .